Triband Compact Printed Antenna for 2.4/3.5/5 GHz WLAN/WiMAX Applications - Pracha Osklang; Chuwong Phongcharoenpanich; Prayoot Akkaraekthalin (My University, 2019)
This research presents a triband compact printed antenna for WLAN and WiMAX applications. The antenna structure consists of a folded open stub, long and short L-shaped strips, and asymmetric trapezoid ground plane. Besides, it is of simple structure and operable in 2.4 GHz and 5 GHz (5.2/5.8 GHz) WLAN and 3.5/5.5 GHz WiMAX bands. The folded open stub and long and short L-shaped strips realize impedance matching at 2.4, 3.5, 5.2, and 5.8 GHz, and the asymmetric trapezoid ground plane fine-tunes impedance matching at 5.2, 5.5, and 5.8 GHz. In addition, the equivalent circuit model consolidated into lumped elements is also presented to explain its impedance matching characteristics. In this study, simulations were carried out, and a prototype antenna was fabricated and experimented. The simulation and experimental results are in good agreement. Specifically, the simulated and experimental radiation patterns are omnidirectional at 2.4, 3.5, and 5.2 GHz and near-omnidirectional at 5.5 and 5.8 GHz. Furthermore, the simulated and measured antenna gains are 1.269–3.074 dBi and 1.10–2.80 dBi, respectively. Essentially, the triband compact printed antenna covers 2.4 GHz and 5 GHz (5.2/5.8 GHz) WLAN and 3.5/5.5 GHz WiMAX frequency bands and thereby is a good candidate for WLAN/WiMAX applications.
Keywords: WiMAX; Ground plane; Stub (electronics); STRIPS; J-pole antenna; Antenna Design and Analysis